2016
DOI: 10.4081/gh.2016.471
|View full text |Cite
|
Sign up to set email alerts
|

Spatial pattern evolution of Aedes aegypti breeding sites in an Argentinean city without a dengue vector control programme

Abstract: The main objective of this study was to obtain and analyse the space-time dynamics of Aedes aegypti breeding sites in Clorinda City, Formosa Province, Argentina coupled with landscape analysis using the maximum entropy approach in order to generate a dengue vector niche model. In urban areas, without vector control activities, 12 entomologic (larval) samplings were performed during three years (October 2011 to October 2014). The entomologic surveillance area represented 16,511 houses. Predictive models for Aed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 35 publications
(51 reference statements)
0
16
0
2
Order By: Relevance
“…Aedes aegypti is a tropical mosquito that has adapted to live and breed in urban environments [5,6]. Ae.…”
Section: Introductionmentioning
confidence: 99%
“…Aedes aegypti is a tropical mosquito that has adapted to live and breed in urban environments [5,6]. Ae.…”
Section: Introductionmentioning
confidence: 99%
“…aegypti infestation and productivity [91]. Espinosa et al [92] used vector breeding, density and cluster data to produce GIS models of Ae. aegypti spatial patterns in Argentina.…”
Section: Resultsmentioning
confidence: 99%
“…Proportion of urban coverage, urban form, and water supply most strongly predicted Ae. aegypti distribution [92]. In a similar modelling study, Little et al [93] found that decaying infrastructure and vegetation levels significantly influenced Ae.…”
Section: Resultsmentioning
confidence: 99%
“…This is considered a robust input to explain vectors abundance [29, 35, 36]. This methodology has been tested for other vectors such as Aedes aegypti [22, 37] but in this study, we developed a specific methodology for Lu. longipalpis that included more variables and the use of a different statistical approach.…”
Section: Discussionmentioning
confidence: 99%
“…The climate is subtropical without a dry season, humid subtropical climate (Cfa) type according to the Köeppen-Greiger classification, with a mean annual median temperature of 23 °C (ranging from -2 °C to 43 °C), and an average annual rainfall of 1300 mm. The driest period in this region is from June to August [22]. Clorinda’s urban area has 53,506 inhabitants distributed in 980 blocks, while Puerto Pilcomayo is an area of 669 inhabitants contiguous to the south-east border of the city where rural-periurban houses are scattered along 11 km on the river bank [23].…”
Section: Methodsmentioning
confidence: 99%